An unprecedented wartime practice: Kodaking the Egyptian Sudan. (September 2018) - Fox, Paul
This article examines Kodak photographs made by participant soldiers and photographer–correspondents working in the field for the illustrated press during the concluding phase of the 1883–1898 campaign to defeat an Islamist insurgency in the Egyptian Sudan, whose leaders sought to create a regional caliphate. It explores how the presence of early generation portable cameras impacted on image making practices on British operations, and how aspects of campaign experience were subsequently represented in Kodak-derived photograph albums. With reference to graphic art and commercial photographic practices associated with Nile tourism and recent military activity in the Nile valley after 1882, the author argues, firstly, that the representation of combat was transformed by handheld photography and, secondly, that in the context of photographs of logistical activity and leisure, picturesque aesthetics were occluded by a 'documentary' mode of representation synonymous with the increasingly industrial nature of Western armed conflict. The article also calls attention to how photomechanical reproduction made possible the widespread availability of affordable albums for a public here identified as the readership of the illustrated general interest weeklies. More generally, the sheer number of photographs resulting from the use of Kodak technology prompted a more fluid use of montage-like techniques by album makers, for public and private use, including text and multiple image combinations, to build more dynamic visual narratives of experience on campaign than had hitherto been possible.